Development and preclinical evaluation of a cable-clamp fixation device for a disrupted pubic symphysis - Martin C. Jordan; David Bröer; Christian Fischer; Philipp Heilig; Fabian Gilbert; Stefanie Hölscher-Doht; Charis Kalogirou; Kevin Popp; Jan-Peter Grunz; Henner Huflage; Rafael G. Jakubietz; Süleyman Ergün; et al. (Communications Medicine, 2022)
Jordan et al. test two titanium cable-clamp implants to reduce pubic symphyseal gapping. Using synthetic bone models and cadaver specimens they show that their implants provide stabilities equivalent to that of a traditional symphyseal plate fixation.